Odpowiedź:
Proszę bardzo! :)
Sprowadzamy liczby do tej samej podstawy w liczniku i mianowniku.
Wtedy możemy skorzystać ze wzoru:
[tex]\frac{a^x}{a^y}=a^{x-y}[/tex]
a)
[tex]\frac{(2^3)^6}{2^1}=\frac{2^{18}}{2^1}=2^{17}[/tex]
b)
[tex]\frac{1}{4}*16^3=\frac{1}{4}*(4^2)^3=\frac{1}{4}*4^6=\frac{4^6}{4^1}=4^5[/tex]
c)
[tex]\frac{1}{3}*9^7=\frac{1}{3}*(3^2)^7=\frac{1}{3}*3^{14}=\frac{3^{14}}{3^1}=3^{13}[/tex]
d)
[tex]\frac{1}{10}*100^4=\frac{1}{10}*(10^2)^4=\frac{1}{10}*10^8=\frac{10^8}{10^1}=10^7[/tex]